Social media analytics for innovation management research: A systematic literature review and future research agenda. (May 2023) - Geissinger, Andrea; Laurell, Christofer; Öberg, Christina; Sandström, Christian
Abstract: New trends in innovation management may require new research methods. Social media analytics (SMA)—a method for capturing and analyzing data from user-generated content published on online platforms—has emerged as a complement or even alternative to more traditional research methods. This article systematically reviews and assesses the use of SMA and its potential for innovation management research. Our results show that use of SMA is still in an emergent phase, although it has become increasingly popular over the past decade. Our literature review illustrates that SMA provides new opportunities for innovation management scholars to enhance customer-, market-, technology-, and society-focused innovation research in several ways. In this paper we develop a research agenda and suggest areas for future research using SMA in innovation management. Highlights: Reviews social media analytics (SMA) for innovation management research. Identifies role of SMA as part of methodological toolkit for customer, market, technology, and society innovation research. Assesses potential role of SMA for innovation management. Suggests how to incorporate SMA into in innovation management research.